BIOCHEMICS Stay Healthy the natural way ... (Homoeopathy for All, 2022)
Tissue Salts are present in extremely small quantities in every cell of the humanbody. Some salts are also found in the intercellular fluids, which nourish the cells and actas a messaging medium for the nervous system. A proper balance of salts withinthe intercellular fluid allows for efficient messaging traffic between the cells andorgans. Mineral salts also assist in the elimination of older, damaged cells andcellular waste products. Mineral salts coat the organs of the body, providenourishment to the elastic fibers and are essential components of bones, teeth andconnective tissues. Without them, nerve cells would fail to form.Cell salts are in ionic form and very digestible. By putting the substance under thetongue it bypasses the digestive juices and goes directly in the bloodstream in thisionic form. The cells recognize this form as useable and immediately suck it intothe cellular membrane. Once enough of the substance has been accepted and thebody is balanced an intake of more cellular salt will do us no harm and be excretedfrom the system. This is not like herb, drug or nutritional supplement where thebody has to expend energy to get rid of the excess.
Keywords: Tissue; drug; body